2018
DOI: 10.1364/boe.9.005703
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of bee venom on human MDA-MB-231 breast cancer cells using Raman spectroscopy

Abstract: We demonstrated the apoptotic effect of bee venom (BV) on human MDA-MB-231 breast cancer cells using Raman spectroscopy and principal component analysis (PCA). Biochemical changes in cancer cells were monitored following BV treatment; the results for different concentrations and treatment durations differed markedly. Significantly decreased Raman vibrations for DNA and proteins were observed for cells treated with 3.0 µg/mL BV for 48 h compared with those of control cells. These results suggest denaturation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…Similar interactions have been demonstrated between melittin and plasma-treated phosphate-buffered saline in MCF7 breast cancer and melanoma cells 19 . Honeybee venom and melittin also induced apoptosis in MCF7 cells 20 , and reduced cell viability and migration in MDA-MB-231 breast cancer cells 21,22 . Honeybee venom reduced metastases of breast cancer to the lung 23 , inhibited tumor growth, and prolonged survival in mice with spontaneous mammary carcinoma tumors 24 .…”
Section: Introductionmentioning
confidence: 95%
“…Similar interactions have been demonstrated between melittin and plasma-treated phosphate-buffered saline in MCF7 breast cancer and melanoma cells 19 . Honeybee venom and melittin also induced apoptosis in MCF7 cells 20 , and reduced cell viability and migration in MDA-MB-231 breast cancer cells 21,22 . Honeybee venom reduced metastases of breast cancer to the lung 23 , inhibited tumor growth, and prolonged survival in mice with spontaneous mammary carcinoma tumors 24 .…”
Section: Introductionmentioning
confidence: 95%
“…In addition, BV intervened in calcium fluctuation, ROS generation, and the release of AIFs and EndoG in human melanoma cells [ 104 ]. In MDA-MB-231 breast cancer, Raman spectroscopy with multivariate analysis proved the effect of nuclear fragmentation and protein degradation at different concentrations [ 105 ]. In summary, with appropriate usage, BV may become a promising antineoplastic drug.…”
Section: Clinical Applications and Mechanism Of Bv Injectionmentioning
confidence: 99%
“…Micro-Raman spectroscopy (Invia, Renishaw, UK) equipped with an inverted microscope was employed to achieve Raman spectral information of individual Jurkat cell, in which a He-Ne laser with the wavelength of 633nm and maximum output power of 50mw was utilized, a microscope objective with the magnification of 50 × and the corresponding laser spot size on each cell was about 1μm in lateral direction and 2 μm in longitudinal direction. The spectral resolution was 0.99cm −1 , due to most of the vibrational spectra of cell biochemical components, such as nucleic acids, lipid, protein, appeared in a fingerprint region of 600 to 1800 cm −1 , based on previous studies [15,16,18,19] and aiming at the main biochemical changes of drug-induced Jurkat cell apoptosis, we only presented and analyzed these Raman peaks in the region of 600 to1800 cm −1 . For each group samples, more than 20 cells were randomly selected, and for each cell, more than three different areas were selected for spectral measurement; for each Raman spectrum, the exposure time was 10s and the accumulated times is set as three.…”
Section: Raman Spectrum and Data Processingmentioning
confidence: 99%
“…Clearly, there were obvious spectral differences between the drugtreated cells and the control group, these peaks at 728, 786, 1092, 1450, 1660cm −1 in the drugtreated cells were lower in intensity than those in the control group while the peaks at 938 and 980cm −1 in the drug-treated cells were higher than those in the control group. And the interpretation of the Raman data was compared with Table 1, a summary from other studies [13][14][15][16][17][18][19][20][21]30,31], in which the intensity decreasing of these peaks at 728, 786 and 1092cm −1 , respectively attributed to the breathing vibrational mode of adenine A, O-P-O stretching vibration of DNA backbone and O-P = O vibration of DNA backbone, revealed that drugs had acted on nucleic acids by destroying the structure of phosphodiester bond of DNA skeleton, breaking the phosphate backbone and inhibiting the synthesis of base pairs. The intensity decreasing of these two peaks at 1003 and 1660cm −1 , respectively attributed to the breathing vibrational mode of phenylalanine and amide I of protein, reflected that DNA structure was destroyed and the synthesis was inhibited, and the translation and transcriptional procedure of protein were suppressed, thus the content of protein was decreased.…”
Section: Fluorescence Imaging and 3d Topographymentioning
confidence: 99%
See 1 more Smart Citation